Regenerative Drive Converter with Line-Frequency Switched Rectifier and without DC Link Components - Sack, Lothar; Piepenbreier, Bernhard (IEEE PESC 04, 2004)
The presented regenerative drive converter consists of a line-side three-phase rectifier and a motor-side three-phase inverter. Antiparallel to the rectifier diodes there are six IGBTs, which conduct the DC link current, if it flows from the inverter to the rectifier. In the DC link there are no components: neither an inductor or an electrolytic capacitor nor a braking resistor or a braking chopper. Between the line and the rectifier there is a filter, comprising a three-phase inductor and three capacitors. As the antiparallel IGBTs are switched with line frequency, their switching pattern is very simple, because it is synchronized with the line voltage. Because of the low additional effort this converter type is very advantageous, when regenerative operation is expected and when low frequency harmonic content of the line current is not critical and does not require a converter with pulsed active front end. The proposed paper describes the basic function of this type of converter. It is shown, that the simple switching pattern for the line-side IGBTs can be generated very easily. The requirements for the line-side filter, its topology and its design are illustrated. A test set-up of this converter with an induction-motor of 7.5 kW is described and experimental results hereof are presented. The DC-link voltage is not ideal, but superimposed by the line-harmonics caused by the rectifier. The resulting influences for the motor can be minimized by means of the PWM strategy of the motor-side inverter. The experimental results show, that the waveforms and the spectrum of the motor voltages and currents and the waveforms and the spectrum of the line currents confirm the theoretical considerations. Measurements of the efficiency of the rectifier show, that its losses are low because of the absence of switching losses. The experimental results show as well, that additional losses of the motor due to the fluctuating DC link voltage are negligible.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEEAS.regene